IMPROVING THE PERFORMANCE OF EDUCATORS AND EDUCATION PERSONNEL THROUGH THE LEARNING COMMUNITY PERSPECTIVE OF PROGRESSIVISM PHILOSOPHY - Yonalia, Revi; Narti, Desmi; Victorizal, Victorizal; Hidayat, Suwarno (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to analyze the strategy for improving the performance of educators and education personnel through the “SMANSA Berbagi” learning community at SMA Negeri 1 Bengkulu Selatan from the perspective of the philosophy of progressivism. The research method used is qualitative with a case study approach. Data collection was carried out through observation, in-depth interviews, and documentation studies. The results of the study obtained were: (1) the strategy to develop educators and education personnel is self-development through the “SMANSA Berbagi” learning community. It was done by sharing knowledge, experiences, and best practices in the learning process. This activity is in line with the principles of the philosophy of progressivism which emphasizes the importance of active, collaborative, and real-experience-oriented learning; (2) The principal always coordinates and collaborates in implementing self-development; (3) performance assessment criteria based on the work result plan (RHK) prepared by each educator and education personnel in PMM; (4) the principal and committee’s strategy to improve the quality of education, by preparing school development plans and participating in monitoring and providing input on the implementation of school programs in order to achieve improvements in the quality of education. This study provides recommendations for schools to continue to support and develop learning communities like this as an effort to improve the quality of education sustainably.